Efficacy and adverse effects of peripheral nerve blocks and local infiltration anesthesia after arthroscopic shoulder surgery: A Bayesian network meta-analysis - Liu, Zheng; Li, Yi-bo; Wang, Ji-hua; Wu, Guang-han; Shi, Peng-cai (Frontiers in Medicine, 2022)
Study objective To quantitatively assess and compare the efficacy and adverse effects of six different peripheral nerve block techniques after arthroscopic shoulder surgery (ASS). Design Bayesian network meta-analysis. Methods The PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure database, Chinese Scientific Journal database, Wan Fang databases were searched to retrieve randomized clinical trials comparing interscalene brachial plexus block, continuous interscalene brachial plexus block, supraclavicular brachial plexus block, suprascapular nerve block, combined suprascapular and axillary nerve block and local infiltration analgesia on postoperative pain, opioid consumption, and adverse effects (defined as Horner’s syndrome, dyspnea, hoarseness, vomiting, and nausea) after ASS under general anesthesia (GA). Two reviewers independently screened the literature, extracted data, and evaluated the risk of bias in the included studies. Results A total of 1,348 articles were retrieved initially and 36 randomized clinical trials involving 3,124 patients were included in the final analysis. The network meta-analysis showed that interscalene brachial plexus block was superior in reducing pain and opioid consumption compared to the five other interventions. However, adverse effects were reduced using suprascapular nerve block and combined suprascapular and axillary nerve block compared to interscalene brachial plexus block. Conclusion Interscalene brachial plexus block was superior in reducing pain and opioid consumption compared to other peripheral nerve blocks but had a higher frequency of adverse events.